Thermogravimetric investigation and selection of catalyst of coal hydrogeneration (International Journal of Biology and Chemistry, 2015)
Thermo gravimetric study of coal in the presence of polymers showed that availability of high asphalt-resinous components – asphaltenes and resins benzene within the temperature of 360 – 443 С in the content was reduced. The optimum catalytics of coal hydrogenation is the compositions on the basis of Pd / C, at which there was the greatest absorption of hydrogen and Co / C, where the hydrogenation rate was maximum.